Slurry, preparation method thereof and substrate precursor
By using slurry containing hexagonal boron nitride powder, dispersant, thickener, adhesive and solvent, wet spraying technology is used to solve the problems of dust pollution and poor bonding in the dry coating process, achieving better sintering effect and environmental protection.
Patent Information
- Application Number
- CN202411873185.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
AI Technical Summary
The dry coating process will produce a large amount of dust during the sintering of ceramic products, and the hexagonal boron nitride powder has poor bonding properties with green bodies and is easy to fall off.
A slurry is provided, including hexagonal boron nitride powder, dispersant, thickener, adhesive and solvent, which is applied to the green body surface by wet spraying technology to form an isolation layer.
This method effectively reduces dust pollution, improves the bonding of hexagonal boron nitride powder and green body, and improves the temperature uniformity and isolation effect of the sintering process.
Smart Images

Figure BDA0005196436390000161 
Figure BDA0005196436390000171 
Figure BDA0005196436390000181
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of slurry, and in particular to a slurry and a preparation method thereof and a substrate precursor. Background Art
[0002] The preparation process of ceramic products involves liquid phase sintering. During the sintering process, if the green bodies such as ceramic substrates are not effectively isolated, the green bodies are prone to bonding after sintering; if the structural parts are not effectively isolated, the temperature uniformity of the sintering process will be affected and unnecessary impurities will be easily introduced. Therefore, the sintering process requires effective isolation of the green body surface.
[0003] In the related art, hexagonal boron nitride powder is generally used to cover an isolation layer on the surface of the green body through a dry coating process. However, the dry coating process will generate a large amount of dust to pollute the environment, and after dry coating, the hexagonal boron nitride powder has poor bonding with the green body and is easy to fall off. Summary of the invention
[0004] The embodiments of the present application provide a slurry and a preparation method thereof and a substrate precursor, which are helpful to solve the problem that a large amount of dust is generated in the dry coating process and the hexagonal boron nitride powder has poor bonding with the green body after dry coating.
[0005] In order to achieve the above objectives, in a first aspect, an embodiment of the present application provides a slurry, which comprises, by mass:
[0006] 10 to 40 parts of hexagonal boron nitride powder;
[0007] 1 to 10 parts of dispersant;
[0008] Thickener 0.01 to 1 part;
[0009] 0.1 to 1 part of adhesive; and
[0010] Solvent 45 to 90 parts.
[0011] Optionally, in some embodiments of the present application, based on 100% of the total mass of the slurry, the slurry includes 10% to 40% of the hexagonal boron nitride powder, 1% to 10% of the dispersant, 0.01% to 1% of the thickener, 0.1% to 1% of the adhesive, and the balance is a solvent.
[0012] Optionally, in some embodiments of the present application, the solvent is water, and the dispersant is a water-soluble dispersant; and / or
[0013] The mass percentage of the hexagonal boron nitride powder is 15wt% to 30wt%; and / or
[0014] The mass percentage of the dispersant is 3wt% to 8wt%.
[0015] Optionally, in some embodiments of the present application, the water-soluble dispersant includes at least one of a polyether dispersant, a polysorbate dispersant, and a cationic dispersant.
[0016] Optionally, in some embodiments of the present application, the polyether dispersant includes at least one of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and polyether type hyperdispersant; and / or
[0017] The polysorbate dispersant includes at least one of polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan monostearate; and / or the cationic dispersant includes at least one of hexadecyltrimethylammonium bromide and octadecyltrimethylammonium chloride.
[0018] Optionally, in some embodiments of the present application, the alkylphenol polyoxyethylene ether includes at least one of TX-10 and OP-10; and / or
[0019] The fatty alcohol polyoxyethylene ether comprises AEO-9; and / or
[0020] The polyether type hyperdispersant includes at least one of polyethylene glycol 400 and polyethylene glycol 3000.
[0021] Optionally, in some embodiments of the present application, the adhesive includes at least one of polyvinyl alcohol (PVA), polyacrylate, polyacrylate emulsion, polyvinyl acetate emulsion and polyurethane.
[0022] Optionally, in some embodiments of the present application, the adhesive includes polyvinyl alcohol (PVA), and the alcoholysis degree of the polyvinyl alcohol (PVA) ranges from 30% to 100%.
[0023] Optionally, in some embodiments of the present application, the thickener includes polyacrylamide, and preferably, the weight average molecular weight of the polyacrylamide is 5 million to 20 million.
[0024] Optionally, in some embodiments of the present application, the D50 particle size of the hexagonal boron nitride powder is 1 μm to 30 μm; and / or
[0025] The hexagonal boron nitride powder is in the form of flakes or spheres.
[0026] Optionally, in some embodiments of the present application, the D50 particle size of the hexagonal boron nitride powder is 1 μm to 10 μm; or
[0027] The D50 particle size of the hexagonal boron nitride powder is 15 μm to 25 μm.
[0028] Optionally, in some embodiments of the present application, the viscosity of the slurry ranges from 1000 cps to 3000 cps.
[0029] In a second aspect, an embodiment of the present application provides a method for preparing a slurry, comprising the following steps:
[0030] According to the mass, 10 to 40 parts of hexagonal boron nitride powder, 1 to 10 parts of dispersant, 0.01 to 1 parts of thickener, 0.1 to 1 parts of adhesive and 45 to 90 parts of solvent are provided for standby use;
[0031] The hexagonal boron nitride powder, dispersant, thickener, adhesive and solvent are stirred to prepare the slurry.
[0032] Optionally, in some embodiments of the present application, the stirring of the hexagonal boron nitride powder, dispersant, thickener, adhesive and solvent comprises the following steps:
[0033] dissolving an adhesive in a solvent and stirring to obtain an adhesive solution;
[0034] adding a dispersant to the adhesive solution to obtain a first dispersion;
[0035] adding hexagonal boron nitride powder to the first dispersion and continuing stirring to obtain a second dispersion;
[0036] A thickener is added to the second dispersion, and stirring is continued to obtain a slurry.
[0037] In a third aspect, an embodiment of the present application provides a substrate precursor, including a green body and an isolation layer prepared by spraying a slurry prepared by the aforementioned slurry or the aforementioned slurry preparation method on the surface of the green body.
[0038] An embodiment of the present application provides a slurry, which includes 10 to 40 parts of hexagonal boron nitride powder; 1 to 10 parts of dispersant; 0.01 to 1 part of thickener; 0.1 to 1 part of adhesive; and 45 to 90 parts of solvent. The slurry prepared according to the above ratio can be wet sprayed, which solves the problem of a large amount of dust generated in the dry coating process; and the slurry has low viscosity, stable state and certain adhesion, which helps to improve the bonding between the hexagonal boron nitride powder and the green body. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0040] Figure 1 is a process flow chart of slurry preparation according to an embodiment of the present application;
[0041] Figure 2 is a process flow chart of preparing a substrate precursor according to an embodiment of the present application;
[0042] Figure 3 is a slurry stable state diagram of Example 1 of the present application;
[0043] Figure 4 This is a diagram of the surface state of the green body after spraying in Example 1 of the present application;
[0044] Figure 5 is a slurry stable state diagram of Comparative Example 1 of the present application;
[0045] Figure 6 This is the surface state diagram of the green body of comparative example 1 of the present application
[0046] Figure 7 This is a slurry stable state diagram of Comparative Example 2 of the present application;
[0047] Figure 8 This is a diagram of the surface state of the green body after slurry spraying in Comparative Example 4 of the present application;
[0048] Fig. 9 This is a diagram of the surface state of the green body after slurry spraying in Comparative Example 6 of the present application;
[0049] Fig.10 is a slurry stable state diagram of Comparative Example 7 of the present application;
[0050] Fig.11 is a slurry stable state diagram of Example 2 of the present application;
[0051] Fig.12 is a slurry stable state diagram of Example 3 of the present application;
[0052] Fig.13 This is a schematic diagram of the appearance of the substrate after sintering and cleaning in Example 1 of the present application;
[0053] Fig.14 This is a schematic diagram of the appearance of the substrate after sintering and cleaning and surface polishing treatment in Example 1 of the present application. DETAILED DESCRIPTION
[0054] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0055] Since hexagonal boron nitride powder is light in weight, a large amount of dust will be generated during the dry coating process. In addition, the hexagonal boron nitride powder after dry coating has poor bonding with the green body and is easy to fall off, resulting in failure of local powder coating.
[0056] In view of this, the present application proposes a slurry, a preparation method thereof, and a substrate precursor.
[0057] According to a first aspect of the present application, a slurry is provided, comprising, by mass:
[0058] 10 to 40 parts of hexagonal boron nitride powder;
[0059] 1 to 10 parts of dispersant;
[0060] Thickener 0.01 to 1 part;
[0061] 0.1 to 1 part of adhesive; and
[0062] Solvent 45 to 90 parts.
[0063] The slurry of the embodiment of the present application includes 10 to 40 parts of hexagonal boron nitride powder, 1 to 10 parts of dispersant, 0.01 to 1 part of thickener, 0.1 to 1 part of adhesive and 45 to 90 parts of solvent. The slurry prepared according to the above ratio can be wet sprayed, which can improve or avoid the problem of large amounts of dust generated by the dry coating process; and the slurry provided in the embodiment of the present application has low viscosity, good stability and certain adhesion, which helps to improve the bonding between the hexagonal boron nitride powder and the green body.
[0064] In some embodiments of the present application, based on 100% of the total mass of the slurry, the slurry may include 10wt% to 40wt% of hexagonal boron nitride powder, 1wt% to 10wt% of a dispersant, 0.01wt% to 1wt% of a thickener, 0.1wt% to 1wt% of a binder, and the remainder being a solvent.
[0065] It should be noted that the mass percentage of each component refers to the mass percentage of the corresponding component in the slurry. Taking hexagonal boron nitride powder as an example, the slurry includes 10wt% to 40wt% of hexagonal boron nitride powder, which means: the mass of the hexagonal boron nitride powder in the slurry is the percentage of the total mass of the slurry.
[0066] In some embodiments of the present application, the slurry includes 10wt% to 40wt% of hexagonal boron nitride powder, that is, the mass percentage of the hexagonal boron nitride powder in the slurry is 10wt% to 40wt%. Exemplarily, the mass percentage of the hexagonal boron nitride powder in the slurry is 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% and any value between the above two values.
[0067] In some embodiments of the present application, the slurry includes 1 wt% to 10 wt% of the dispersant, that is, the mass percentage of the dispersant in the slurry is 1 wt% to 10 wt%. Exemplarily, the mass percentage of the dispersant in the slurry is 1 wt%, 3 wt%, 5 wt%, 8 wt%, 10 wt% and any value between the above two values.
[0068] In some embodiments of the present application, the slurry includes 0.01wt% to 1wt% of a thickener, that is, the mass percentage of the thickener in the slurry is 0.01wt% to 1wt%. Exemplarily, the mass percentage of the thickener in the slurry is 0.01wt%, 0.05wt%, 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt% and any value between the above two values.
[0069] In some embodiments of the present application, the slurry includes 0.1wt% to 1wt% of a binder, that is, the mass percentage of the binder in the slurry is 0.01wt% to 1wt%. Exemplarily, the mass percentage of the binder in the slurry is 0.01wt%, 0.05wt%, 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt% and any value between the above two values.
[0070] In some embodiments of the present application, the mass percentage of the hexagonal boron nitride powder in the slurry may be 15wt% to 30wt%. The slurry prepared by the hexagonal boron nitride powder in the above range has a moderate viscosity.
[0071] In some embodiments of the present application, the mass percentage of the dispersant may be 3wt% to 8wt%. The above mass percentage of the dispersant helps to further promote the full dissolution of the hexagonal boron nitride powder in the solvent, so that the prepared slurry has no particle agglomeration or sedimentation.
[0072] In some embodiments of the present application, the mass percentage of the hexagonal boron nitride powder in the slurry may be 15 wt % to 30 wt %, and the mass percentage of the dispersant may be 3 wt % to 8 wt %.
[0073] The embodiment of the present application further selects the mass percentage of the hexagonal boron nitride powder and the mass percentage of the dispersant so that the prepared slurry has moderate viscosity and good adhesion, which helps to further improve the bonding of the hexagonal boron nitride powder on the surface of the green body.
[0074] In some embodiments of the present application, the solvent may be water, and the dispersant may be a water-soluble dispersant.
[0075] The solvent of the embodiment of the present application is water, which helps to achieve green and environmental protection of the slurry. At the same time, because the spraying process is in a closed space, it also helps to reduce the explosion risk of the slurry. Accordingly, the dispersant uses a water-soluble dispersant, which has good affinity with the water-based solvent, which is conducive to improving the dispersion effect of each component in the slurry.
[0076] In some embodiments of the present application, the water-soluble dispersant includes at least one of a polyether dispersant, a polysorbate dispersant, and a cationic dispersant.
[0077] Optionally, the polyether dispersant includes at least one of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and polyether type hyperdispersant.
[0078] Optionally, the polysorbate dispersant includes polyoxyethylene sorbitan monolaurate or polyoxyethylene sorbitan monostearate.
[0079] Optionally, the cationic dispersant includes hexadecyltrimethylammonium bromide or octadecyltrimethylammonium chloride.
[0080] It can be understood that the alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, polyether-type hyperdispersant, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monostearate, hexadecyltrimethylammonium bromide or octadecyltrimethylammonium chloride in the embodiments of the present application all have good emulsification and dispersing effects, and these dispersants have good compatibility with the adhesive used, and the above-mentioned dispersants will not react with the substrate.
[0081] In some embodiments of the present application, the alkylphenol polyoxyethylene ether may include at least one of TX-10 and OP-10.
[0082] It is understood that TX-10 refers to alkylphenol polyoxyethylene ether TX-10, and OP-10 refers to alkylphenol polyoxyethylene ether OP-10.
[0083] In some embodiments of the present application, the fatty alcohol polyoxyethylene ether may include AEO-9.
[0084] It can be understood that AEO-9 is the abbreviation of fatty alcohol polyoxyethylene ether-9, which is a dispersant made by addition reaction of fatty alcohol and ethylene oxide. There are 9 ethylene oxide groups in its molecular structure, so it is called AEO-9.
[0085] It should be noted that in addition to being a dispersant, AEO-9 can also be used as a hydrophilic emulsifier, which can reduce interfacial free energy, form a firm emulsion film, prevent droplet aggregation and solubilization. The more neatly the hydrophilic emulsifier is arranged around the droplets, the firmer the emulsion film and the more stable the emulsion, thereby inhibiting the sedimentation of large-particle hexagonal boron nitride powder, solving the problem that large-particle hexagonal boron nitride powder is difficult to disperse evenly and easy to settle in the wet process.
[0086] In some embodiments of the present application, the D50 particle size of the hexagonal boron nitride powder is 10 μm to 30 μm, and the dispersant includes fatty alcohol polyoxyethylene ether.
[0087] It should be noted that hexagonal boron nitride powder with a particle size of 10 μm to 30 μm can be considered as large-particle hexagonal boron nitride powder, and large-particle hexagonal boron nitride is very prone to agglomeration and sedimentation after the slurry is left to stand for 3 hours. The embodiment of the present application uses fatty alcohol polyoxyethylene ether as a dispersant, which can not only play a dispersing role, but also play a hydrophilic emulsifying role, which helps to solve the problem that large-particle hexagonal boron nitride powder is difficult to disperse and easy to settle.
[0088] In some embodiments of the present application, the polyether hyperdispersant may include at least one of polyethylene glycol 400 and polyethylene glycol 3000.
[0089] In some embodiments of the present application, the adhesive includes at least one of polyvinyl alcohol (PVA), polyacrylate, polyacrylate emulsion, polyvinyl acetate emulsion and polyurethane.
[0090] It is understandable that the addition of adhesive will make the hexagonal boron nitride powder have a certain degree of adhesion, and after drying it can adhere firmly to the surface of the green body. In the subsequent process of lamination and green body transfer device, it is helpful to prevent the hexagonal boron nitride powder from falling off the surface of the green body, thereby causing the isolation effect to deteriorate or the surface of the green body to deform.
[0091] It should be noted that adding an adhesive to the slurry can increase the viscosity of the slurry, which is not conducive to the uniform dispersion of the slurry. The inventors found through research that adding fatty alcohol polyoxyethylene ether to the slurry can help solve the problem of preventing the large-particle boron nitride powder from settling, while also solving the negative effects of adding an adhesive.
[0092] In some embodiments of the present application, the alcoholysis degree of polyvinyl alcohol PVA ranges from 30% to 100%. Further, the alcoholysis degree of polyvinyl alcohol PVA ranges from 30% to 60%, 60% to 75%, or 75% to 100%. Exemplarily, the alcoholysis degree of polyvinyl alcohol PVA is 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, and any value between two adjacent values.
[0093] The alcoholysis degree of the polyvinyl alcohol (PVA) in the embodiment of the present application ranges from 30% to 100%. When the hexagonal boron nitride powder sprayed on the surface of the green body is relatively light in weight, a certain degree of adhesion can be achieved to prevent the hexagonal boron nitride powder from being missing during the stacking process of the green body after the slurry is dried.
[0094] It should be noted that the polyvinyl alcohol (PVA) with an alcoholysis degree ranging from 75% to 100% has excellent adhesion, and the polyvinyl alcohol (PVA) within this alcoholysis degree range also has good miscibility with the dispersant, which helps to improve the uniformity of the slurry.
[0095] In some embodiments of the present application, the thickener may include polyacrylamide.
[0096] It should be noted that polyacrylamide is a water-based thickener and has good compatibility with water and water-soluble dispersants. Moreover, polyacrylamide can adjust the viscosity of the slurry so that the slurry can be sprayed on the surface of the green body, thereby ensuring a uniform and stable state on the surface of the green body.
[0097] Further, the weight average molecular weight of polyacrylamide can be 5 million to 20 million. Further, the weight average molecular weight of polyacrylamide is 10 million to 15 million. Exemplarily, the weight average molecular weight of polyacrylamide is 5 million, 6 million, 7 million, 8 million, 9 million, 10 million, 11 million, 12 million, 13 million, 14 million, 15 million, 16 million, 17 million, 18 million, 19 million, 20 million and any value between two adjacent values.
[0098] It should be noted that polyacrylamide with a weight average molecular weight of 5 million to 20 million has good miscibility with the dispersant, which helps to improve the uniformity of the slurry.
[0099] In some embodiments of the present application, the D50 particle size of the hexagonal boron nitride powder may be 1 μm to 30 μm.
[0100] It can be understood that the D50 particle size range of the hexagonal boron nitride powder of the present application spans a large range, and the D50 particle size of the hexagonal boron nitride powder can be 1 μm, 30 μm, or any value within the range of 1 μm to 30 μm.
[0101] It is understandable that the larger the powder particle size, the smaller the particle surface energy, the more difficult it is for the powder to disperse in the slurry, and under long-term static conditions, particle agglomeration and sedimentation will occur. The hexagonal boron nitride powder of the embodiment of the present application can be of large particle size or small particle size. Small-particle hexagonal boron nitride powder generally refers to hexagonal boron nitride powder with a particle size less than or equal to 10 μm, and large-particle hexagonal boron nitride powder generally refers to hexagonal boron nitride powder with a particle size greater than or equal to 10 μm. Exemplarily, the particle size of the hexagonal boron nitride powder is 15 μm to 25 μm. Large-particle hexagonal boron nitride powder helps to maintain better high-temperature stability and lubrication effect, so as to better achieve isolation and lubrication effects.
[0102] In some embodiments of the present application, the hexagonal boron nitride powder is in the form of flakes or spheres.
[0103] It can be understood that flake and spherical are two morphological types of hexagonal boron nitride powder. The particle size range of flake hexagonal boron nitride powder is relatively wide, and it is easy to achieve uniform dispersion in both water-based and alcohol-based solvents; the particle size of spherical hexagonal boron nitride powder is larger, and the isolation effect is better.
[0104] In some embodiments of the present application, the D50 of the hexagonal boron nitride powder is 1 μm to 10 μm. Exemplarily, the D50 of the hexagonal boron nitride powder is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, and any value between the above two values.
[0105] In some embodiments of the present application, the D50 particle size of the hexagonal boron nitride powder is 15 μm to 25 μm. Exemplarily, the D50 of the hexagonal boron nitride powder is 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, and any value between the above two values.
[0106] In some embodiments of the present application, the D50 particle size of the hexagonal boron nitride powder is 10 μm to 30 μm, and the dispersant includes fatty alcohol polyoxyethylene ether.
[0107] It should be noted that for hexagonal boron nitride powder with a D50 particle size of 10 μm to 30 μm, due to the large particle size, the solubility of the hexagonal boron nitride powder in the formulation system and the stability of the target product may be affected. At this time, the dispersant is selected as fatty alcohol polyoxyethylene ether, which can be used as a dispersant and a hydrophilic emulsifier, which helps to promote the dispersion of large-particle hexagonal boron nitride powder and also inhibits the sedimentation of large-particle hexagonal boron nitride powder.
[0108] In some embodiments of the present application, the viscosity of the slurry ranges from 1000cps to 3000cps. For example, the viscosity of the slurry is 1000cps, 1200cps, 1500cps, 1800cps, 2000cps, 2300cps, 2500cps, 2700cps, 3000cps and any value between the above two values. It should be noted that the viscosity of the slurry in the embodiments of the present application can be obtained by testing according to the liquid viscosity test method of GB / T 22235-2008.
[0109] The viscosity of the slurry in the embodiment of the present application ranges from 1000cps to 3000cps, which can achieve the hexagonal boron nitride droplets to be sprayed in a mist-like discrete form during the spraying process, ensuring that the hexagonal boron nitride powder attached to the surface of the green body after spraying is uniform. When the viscosity is too low, large particle droplets are easily formed during spraying, resulting in uneven watermarks, lines and other uneven phenomena on the surface of the green body after spraying, which may eventually lead to unevenness or bonding problems on the substrate after sintering; when the viscosity is too high, the slurry is easy to agglomerate, and it is easy to block the pipeline or nozzle during pumping, resulting in the inability to spray continuously.
[0110] In a second aspect, an embodiment of the present application provides a method for preparing a slurry, comprising the following steps:
[0111] S100, providing 10 to 40 parts of hexagonal boron nitride powder, 1 to 10 parts of a dispersant, 0.01 to 1 parts of a thickener, 0.1 to 1 parts of an adhesive, and 45 to 90 parts of a solvent, by mass, for standby use;
[0112] S200, stirring the above-mentioned hexagonal boron nitride powder, dispersant, thickener, adhesive and solvent to prepare slurry.
[0113] See also Figure 1 In some embodiments of the present application, the preparation method may include the following steps:
[0114] Weighing materials: providing the components of the slurry as described in the first aspect;
[0115] Sol: dissolve the adhesive in deionized water and stir to obtain an adhesive aqueous solution;
[0116] Dispersing: adding a dispersant to the adhesive aqueous solution and continuing stirring to obtain a first dispersion;
[0117] Powder preparation: add hexagonal boron nitride powder to the first dispersion, and continue stirring until there is no particle agglomeration or deposition on the surface of the dispersion to obtain a second dispersion;
[0118] Thickening: Add a thickener to the second dispersion and continue stirring to obtain a slurry.
[0119] In some embodiments of the present application, in the sol step, stirring is performed at a temperature of 60° C. to 100° C. Exemplarily, stirring is performed at a temperature of 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C., 100° C., and any value between the above two values. This helps to promote the dissolution of polyvinyl alcohol PVA.
[0120] In some embodiments of the present application, in the sol step, the stirring speed is 500r / min to 800r / min, and the stirring time is 2h to 10h. Exemplarily, the stirring speed is 500r / min, 550r / min, 600r / min, 650r / min, 700r / min, 750r / min, 800r / min and any value between any two of the above values. Exemplarily, the stirring time is 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h and any value between any two of the above values.
[0121] In some embodiments of the present application, in the dispersion step, the stirring speed is consistent with the stirring speed in the sol step, and the stirring time is 1 hour to 5 hours.
[0122] In some embodiments of the present application, in the powder mixing step, the stirring speed is consistent with the stirring speed in the dispersion step, and the stirring time is 3 hours to 10 hours.
[0123] In some embodiments of the present application, in the powder preparation step, after adding hexagonal boron nitride powder to the first dispersion, heating can be stopped and stirring can be continued until there is no particle agglomeration or deposition on the surface of the dispersion to obtain a second dispersion.
[0124] In some embodiments of the present application, in the thickening step, the stirring speed is consistent with the stirring speed in the powder mixing step, and the stirring time is 1 hour to 5 hours.
[0125] In a third aspect, an embodiment of the present application provides a substrate precursor, including a green body and an isolation layer prepared by spraying a slurry prepared by the aforementioned slurry or the aforementioned slurry preparation method on the surface of the green body. The substrate precursor of the embodiment of the present application has hexagonal boron nitride powder on its surface that can be uniformly adsorbed, and the powder coating state of the green body surface is consistent.
[0126] It should be noted that, when the substrate of the embodiment of the present application is mass-produced, the isolation layer can effectively play an isolation role, thereby solving the problem of easy adhesion and deformation of multi-layer stacked green bodies during sintering.
[0127] In some embodiments of the present application, the green body may be a green body sheet, a green body block or other green bodies of different shapes.
[0128] In some embodiments of the present application, the green body material may be a nitride ceramic material. For example, the nitride ceramic material may be silicon nitride or aluminum nitride.
[0129] The formula of the present application can also be expanded. For example, hexagonal boron nitride powder and deionized water are used as the main raw materials, and matched with the organic systems such as the dispersant, adhesive, thickener, etc. of the present application, to explore suitable formulas, so that silk screen printing equipment can be continuously produced, and screen plates of suitable sizes can be customized to achieve silk screen printing on the surface of the green body, thereby greatly reducing costs.
[0130] The present application is described in detail below by means of specific examples, which are only partial examples of the present application and are not intended to limit the present application. The raw materials used in the following examples are all commercially available products unless otherwise specified.
[0131] Example 1
[0132] A slurry is prepared by the following method:
[0133] Weighing: Weigh 20 parts of hexagonal boron nitride powder, 5 parts of fatty alcohol polyoxyethylene ether dispersant, 1 part of polyvinyl alcohol PVA, 0.1 part of polyacrylamide and 73.9 parts of water; wherein the particle size of the hexagonal boron nitride powder is 15 μm to 25 μm, the fatty alcohol polyoxyethylene ether dispersant is AEO-9, the alcoholysis degree of polyvinyl alcohol PVA is 75% to 100%, and the weight average molecular weight of polyacrylamide is 10 million to 15 million;
[0134] Sol: Add weighed adhesive and deionized water into a sealed stirring barrel, place in a water bath at 80°C for stirring, with the stirring blade speed between 500r / min and 800r / min, stir for 2h to 10h, until the adhesive is completely dissolved and the stirring is stopped to obtain an adhesive solution, which is transparent without obvious white particles precipitated;
[0135] Dispersion: Add dispersant to the adhesive solution, keep the rotation speed and temperature constant, stir for 1 to 5 hours, and stop stirring when the dispersant is completely dissolved to obtain a first dispersion, which is yellow-brown;
[0136] Powder preparation: Add fully weighed hexagonal boron nitride powder to the first dispersion, turn off the water bath heating, keep the stirring blade speed unchanged, stir for 3 to 10 hours, stop stirring when there is no obvious suspended particles in the slurry, and obtain the second dispersion. Test the second dispersion through a 300 to 800 mesh sieve. If there is no large particle clogging, the slurry preparation is considered normal;
[0137] Thickening: Add a thickener to the second dispersion, keep the stirring blade speed unchanged, stir for 1 to 5 hours, and stop stirring until there is no obvious particle agglomeration or sedimentation in the slurry state to obtain a slurry.
[0138] Embodiment 2:
[0139] A slurry, which differs from Example 1 in that the slurry formula is different. The formula of this example is as follows: 30 parts of hexagonal boron nitride powder, 8 parts of fatty alcohol polyoxyethylene ether dispersant, 1 part of polyvinyl alcohol PVA, 0.2 parts of polyacrylamide and 60.8 parts of water are weighed; wherein the particle size of the hexagonal boron nitride powder is 1 μm to 10 μm, the fatty alcohol polyoxyethylene ether dispersant is AEO-9, the alcoholysis degree of polyvinyl alcohol PVA is 75% to 100%, and the weight average molecular weight of polyacrylamide is 10 million to 15 million;
[0140] Embodiment 3:
[0141] A slurry, which is different from Example 2 in that the particle size of the hexagonal boron nitride powder is different. In this example, the particle size of the hexagonal boron nitride powder is 15 μm to 25 μm.
[0142] Embodiment 4:
[0143] A slurry, which is different from Example 3 in that the type of dispersant is different. The dispersant of this example is polyethylene glycol 400.
[0144] Embodiment 5:
[0145] A slurry, which is different from Example 3 in that the range of alcoholysis degree of the adhesive is different. The alcoholysis degree of the adhesive in this example is 30% to 60%.
[0146] Embodiment 6:
[0147] A slurry, which differs from Example 1 in that the slurry has a different formula. The formula of this example includes 10 parts of hexagonal boron nitride powder, 1 part of fatty alcohol polyoxyethylene ether dispersant, 1 part of polyvinyl alcohol PVA, 0.1 part of polyacrylamide and 87.9 parts of water.
[0148] Embodiment 7:
[0149] A slurry, which differs from Example 1 in that the slurry has a different formula. The formula of this example includes 40 parts of hexagonal boron nitride powder, 10 parts of fatty alcohol polyoxyethylene ether dispersant, 1 part of polyvinyl alcohol PVA, 0.1 parts of polyacrylamide and 48.9 parts of water.
[0150] Embodiment 8:
[0151] A slurry, which is different from Example 1 in that the slurry has a different formula.
[0152] The formula of this embodiment includes 20 parts of hexagonal boron nitride powder, 5 parts of fatty alcohol polyoxyethylene ether dispersant, 0.1 parts of polyvinyl alcohol PVA, 0.1 parts of polyacrylamide and 74.8 parts of water.
[0153] Comparative Example 1
[0154] A slurry, which is different from Example 1 in that the slurry formula is different.
[0155] The formula of this comparative example includes 5 parts of hexagonal boron nitride powder, 5 parts of fatty alcohol polyoxyethylene ether dispersant, 1 part of polyvinyl alcohol PVA, 0.1 part of polyacrylamide and 88.9 parts of water.
[0156] Comparative Example 2:
[0157] A slurry, which is different from Example 1 in that the slurry formula is different.
[0158] The formula of this comparative example includes 50 parts of hexagonal boron nitride powder, 5 parts of fatty alcohol polyoxyethylene ether dispersant, 1 part of polyvinyl alcohol PVA, 0.1 part of polyacrylamide and 43.9 parts of water.
[0159] Comparative Example 3:
[0160] A slurry, which is different from Example 1 in that the slurry has a different formula.
[0161] The formula of this comparative example includes 20 parts of hexagonal boron nitride powder, 0.5 parts of fatty alcohol polyoxyethylene ether dispersant, 1 part of polyvinyl alcohol PVA, 0.1 parts of polyacrylamide and 78.4 parts of water.
[0162] Comparative Example 4:
[0163] A slurry, which is different from Example 1 in that the slurry formula is different.
[0164] The formula of this comparative example includes 20 parts of hexagonal boron nitride powder, 15 parts of fatty alcohol polyoxyethylene ether dispersant, 1 part of polyvinyl alcohol PVA, 0.1 part of polyacrylamide and 63.9 parts of water.
[0165] Comparative Example 5;
[0166] A slurry, which is different from Example 1 in that the slurry has a different formula.
[0167] The formula of this comparative example includes 20 parts of hexagonal boron nitride powder, 5 parts of fatty alcohol polyoxyethylene ether dispersant, 5 parts of polyvinyl alcohol PVA, 0.1 parts of polyacrylamide and 69.9 parts of water.
[0168] Comparative Example 6:
[0169] A slurry, which is different from Example 1 in that the slurry has a different formula.
[0170] The formula of this comparative example includes 20 parts of hexagonal boron nitride powder, 5 parts of fatty alcohol polyoxyethylene ether dispersant, 1 part of polyvinyl alcohol PVA, 0.005 parts of polyacrylamide and 74 parts of water.
[0171] Comparative Example 7:
[0172] A slurry, which is different from Example 1 in that the slurry has a different formula.
[0173] The formula of this comparative example includes 20 parts of hexagonal boron nitride powder, 5 parts of fatty alcohol polyoxyethylene ether dispersant, 1 part of polyvinyl alcohol PVA, 5 parts of polyacrylamide and 69.9 parts of water.
[0174] Performance Test:
[0175] 1. Sample preparation:
[0176] See also Figure 2 , Loading: Add the slurry prepared in the embodiment and the comparative example into the loading bucket of the powder coating machine, turn on the heating and stirring, set the temperature to 60°C, and the stirring speed to 100r / min to 300r / min;
[0177] Weighing of green sheets: Randomly select 10 green sheets, mark them with numbers, weigh them with a balance, and record the weight of the green sheets with an accuracy of at least 0.01g;
[0178] Process settings: The centrifugal pump feeding pressure is between 0.1 and 0.5 MPa, the main spray pressure is between 0.05 and 0.3 MPa, the nozzle atomization pressure is between 0.1 and 0.5 MPa, the drying temperature of the long drying tunnel is between 40 and 100 ° C, and the conveyor belt speed is between 800 and 1500 mm / min. The slurry can be normally fed and refluxed for continuous spraying and drying.
[0179] Spray coating: Place the green sheet at the conveyor belt feed port, start the powder coating machine, and the conveyor belt starts to rotate. The hexagonal boron nitride slurry is evenly atomized on the surface of the green sheet, and then dried in a long drying tunnel. Finally, the hexagonal boron nitride powder is evenly adhered to the surface of the green sheet, with a thickness ranging from 15μm to 50μm.
[0180] Green sheet inspection: Screen the surface of the green sheet after powder coating, requiring no obvious particle protrusions or corrugated defects on the surface. Weigh the 10 pieces numbered in the early stage, requiring the weight of a single piece of powder coating to be between 0.2g and 0.3g;
[0181] Degreasing preparation: The green sheets that have passed the above tests are stacked according to the predetermined number of layers, which must be uniform and without corner overflow. The hexagonal boron nitride powder should not be damaged during the process, and other impurities should not be introduced.
[0182] The green sheets sprayed in batches according to the above process have excellent surface conditions, no obvious particle precipitation or corrugated defects, and can be easily separated after sintering. The hexagonal boron nitride powder on the surface of the substrate can be easily removed after simple water washing or brushing, and the appearance quality of the substrate is greatly improved.
[0183] 2. Detection method:
[0184] 1. Viscosity test: The viscosity of the slurries of the embodiments and comparative examples was tested according to the liquid viscosity test method of GB / T 22235-2008.
[0185] 2. Powder weight test:
[0186] Using the electronic balance test method of GB / T 26497-2022, 10 green sheets are weighed, numbered, and weighed on a balance. The weight of the green sheets before powder coating and after drying is weighed separately, with an accuracy of at least 0.01g. The difference is the weight of the powder on the surface of the green sheet.
[0187] 3. Green body inspection: Screen the green body sheets after the powder coating, requiring that there are no obvious particle protrusions or corrugated defects on the surface, and weigh the 10 pieces numbered in the early stage, requiring the weight of a single powder-coated piece to be between 0.2g and 0.3g.
[0188] 4. Stack test:
[0189] The qualified green sheets are stacked in a predetermined number of layers, which are required to be neat and uniform without corner overflow, and the hexagonal boron nitride powder is not damaged and other impurities are not introduced during the process.
[0190] 5. Adhesion test:
[0191] Test the dried green body by turning the powdered surface upside down or placing it under a fan to see if any powder is blown away. Use your fingers to wipe it with a force of 10 to 50N to see if there are any obvious signs of erasure.
[0192] 6. Isolation effect test:
[0193] The sintered substrates are separated. If they can be easily separated with both hands, the effect is good. If tools such as blades are needed, the isolation effect is poor. If the substrates are bonded and cannot be separated, there is no isolation effect.
[0194] 7. Particle size test:
[0195] The solid particle size distribution was determined by the GB / T 13220-91 sonic sieving method.
[0196] 3. Test results:
[0197] The slurries of Examples 1 to 8 and Comparative Examples 1 to 7 were allowed to stand at room temperature for 3 hours, the viscosity was tested, and the slurry stability, spraying state, and green body surface state after spraying were observed. The test results are shown in Table 1.
[0198] Table 1
[0199]
[0200]
[0201]
[0202] Combined with Example 1, Table 1 and Figure 3-4 The test results show that the slurry prepared by the formula of this application has a moderate concentration, the hexagonal boron nitride powder in the slurry is fully dispersed, and there is no obvious particle sedimentation. When spraying, the slurry is sprayed on the green body in a mist form. After drying, the hexagonal boron nitride powder on the surface of the green body is evenly adsorbed, and the powder coating state on the surface of the green body is consistent. Figure 13-14 The test results show that the green body sprayed according to the method of the present application can be easily separated after sintering, and the hexagonal boron nitride powder on the surface of the substrate can be removed by simple water washing or brushing. The surface of the obtained substrate has no obvious particles or defects, which greatly improves the appearance quality of the substrate.
[0203] Compared with Example 1, Comparative Example 1 reduces the content of hexagonal boron nitride powder, which will lead to too thin viscosity of the slurry. Figure 5-6 The test results show that the slurry cannot be sprayed in a mist form, and liquid flow can be clearly observed on the surface of the green body, leaving corrugated defects.
[0204] Comparative Example 2 Compared with Example 1, Comparative Example 2 increases the content of hexagonal boron nitride powder, which will cause the viscosity of the slurry to be too thick. Figure 7 The test results show that the slurry cannot be effectively sprayed.
[0205] Compared with Example 1, Comparative Example 3 reduces the content of the fatty alcohol polyoxyethylene ether dispersant. Combined with the test results in Table 1, it can be seen that the hexagonal boron nitride powder will agglomerate and settle after standing for a short period of time; the slurry cannot be sprayed effectively, causing pipeline blockage.
[0206] Comparative Example 4 Compared with Example 1, Comparative Example 4 increases the content of the fatty alcohol polyoxyethylene ether dispersant, that is, when the content of the fatty alcohol polyoxyethylene ether dispersant is too high, combined with Table 1 and Figure 8 It can be seen from the test results that the slurry cannot be sprayed effectively, and liquid flow can be clearly observed on the surface of the green body, leaving corrugated defects.
[0207] Compared with Example 1, Comparative Example 5 increases the content of the adhesive, which also leads to a higher viscosity of the slurry. Combined with the test results in Table 1, it can be seen that the hexagonal boron nitride powder cannot be fully dispersed, and there are obvious particle agglomeration and sedimentation phenomena. After standing, it cannot be stirred and dispersed with a glass rod, and there is slight colloid precipitation; the slurry cannot be effectively sprayed, which will cause pipeline blockage.
[0208] Comparative Example 6 Compared with Example 1, Comparative Example 6 reduces the content of thickener, resulting in a too thin viscosity of the slurry. Fig. 9 The test results show that the slurry cannot be sprayed out in a mist form, and liquid flow can be clearly observed on the surface of the green body, leaving corrugated defects.
[0209] Comparative Example 7 Compared with Example 1, Comparative Example 7 increases the content of thickener, resulting in excessive viscosity of the slurry. Fig.10 The test results show that the slurry cannot be effectively sprayed on the surface of the green body.
[0210] In summary, the viscosity of the slurry is related to the spraying effect. When the slurry viscosity is moderate, about 1000cps to 3000cps, the slurry is well dispersed without agglomeration or sedimentation, and the slurry state is stable, which can ensure that the hexagonal boron nitride powder attached to the surface of the green body after spraying is uniform. When the viscosity is too low, large particle droplets are easily formed during spraying, resulting in uneven watermarks, textures and other uneven phenomena on the surface of the green body after spraying, which may eventually lead to unevenness or bonding problems on the substrate after sintering; when the viscosity is too high, the slurry is easy to agglomerate, and it is easy to block the pipeline or nozzle during pumping, resulting in inability to spray continuously.
[0211] Compared with Example 1, Example 2 changes the content of each component in the formula. Fig.11 The test results show that the hexagonal boron nitride powder can be fully dispersed without obvious particle sedimentation. The slurry is sprayed out in a mist-like discrete state, and the hexagonal boron nitride powder is evenly adsorbed on the surface of the green body, and the powder coating state of the green body surface is consistent.
[0212] Compared with Example 2, Example 3 increases the particle size of the hexagonal boron nitride powder, and uses hexagonal boron nitride powder of 15 μm to 25 μm to prepare the slurry. Fig.12The test results show that there is no particle precipitation or sedimentation in the slurry after standing for 3 hours; the slurry can be sprayed out in a mist-like discrete form, and the hexagonal boron nitride powder is uniformly adsorbed on the surface of the green body, and the powder coating state of the green body surface is consistent. It shows that the fatty alcohol polyoxyethylene ether can be used as a dispersant and emulsifier to disperse the large-particle hexagonal boron nitride powder in water into extremely small droplets. The emulsifier is adsorbed around the droplets and arranged in a directional film around the droplets, thereby reducing the interfacial tension and effectively preventing the droplets from aggregating. The emulsifier can reduce the interfacial free energy, form a firm emulsified film, prevent the droplets from aggregating and solubilizing, and help improve the stability of the emulsion. The more stable the emulsion is, the more it helps to inhibit the sedimentation of large-particle hexagonal boron nitride powder, so that the slurry remains stable for a long time.
[0213] Compared with Example 3, in Example 4, the dispersant used is polyethylene glycol 400, which can be dissolved in water to achieve good dispersion. However, a small amount of bubbles are generated in the prepared slurry, which settles slightly after standing for 3 hours and can be evenly dispersed after stirring. The slurry can be effectively sprayed, and the powder coating state on the surface of the green body can be guaranteed to be consistent, and the hexagonal boron nitride powder is evenly adsorbed on the surface of the green body.
[0214] Combined with the test results in Table 1, it can be seen that polyethylene glycol can be fully dissolved in water, and the slurry can achieve good dispersion, but there are a small amount of bubbles in the slurry, and there is a slight particle sedimentation phenomenon after standing for 3 hours. It can be seen that the use of fatty alcohol polyoxyethylene ether dispersant has good hydrophilicity and good emulsification relative to polyethylene glycol, which helps to inhibit the precipitation and sedimentation of particles, and does not chemically react with other substances in the slurry.
[0215] Compared with Example 3, Example 5 uses polyvinyl alcohol PVA with a degree of alcoholysis of 30% to 60% as an adhesive, and the hexagonal boron nitride powder in the slurry is fully dispersed, and there is no obvious particle sedimentation phenomenon. The slurry is sprayed in a mist form. After spraying, the hexagonal boron nitride powder is uniformly adsorbed on the surface of the green body. The hexagonal boron nitride powder is uniformly adsorbed, and the adhesion of the hexagonal boron nitride powder is slightly worse than that of Example 1. If the green body is strongly rubbed during lamination or transportation, it is easy to cause the powder to fall off. After drying, the hexagonal boron nitride powder on the surface of the green body has better adhesion. There is no obvious powder blowing or removal when the green body is inverted or placed under a fan, but the hexagonal boron nitride powder on the surface of the green body has obvious traces of wiping when the finger is wiped with a force of 10N to 50N.
[0216] Compared with Example 3, in Example 6, the content of hexagonal boron nitride powder is 10 parts and the dispersant is 1 part. The slurry prepared in Example 6 is in a stable state, and the hexagonal boron nitride powder is evenly dispersed without obvious agglomeration or particle sedimentation. The slurry is sprayed out in a mist-like discrete type, and after spraying, the powder coating state on the surface of the green body is consistent.
[0217] Compared with Example 3, in Example 7, the content of hexagonal boron nitride powder is 40 parts, and the content of dispersant is 10 parts. The hexagonal boron nitride powder in the slurry prepared in Example 7 is fully dispersed, and there is slight agglomeration after standing for 3 hours, but it can be restored by stirring at room temperature; the slurry is sprayed out in a mist-like discrete type, and after spraying, the powder coating state of the green body surface is consistent.
[0218] Compared with Example 3, when the content of polyvinyl alcohol (PVA) in Example 8 is 0.1%, the hexagonal boron nitride powder is fully dispersed, there is no obvious particle sedimentation, the slurry viscosity is appropriate, and it is sprayed on the green body in a mist form. When the green body is turned upside down or placed under a fan, there is no obvious powder blowing or removal. However, when the fingers are used to wipe with a force of 10N to 50N, the hexagonal boron nitride powder on the surface of the green body has obvious traces of wiping.
[0219] The above is a detailed introduction to a slurry and its preparation method and substrate precursor provided in the embodiments of the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A slurry, characterized in that: In terms of quality, it includes: 10 to 40 parts of hexagonal boron nitride powder; 1 to 10 parts of dispersant; Thickener 0.01 to 1 part; 0.1 to 1 part of adhesive; and Solvent 45 to 90 parts.
2. The slurry according to claim 1, characterized in that Based on 100% of the total mass of the slurry, the slurry includes 10% to 40% of the hexagonal boron nitride powder, 1% to 10% of a dispersant, 0.01% to 1% of a thickener, 0.1% to 1% of a binder, and the balance is a solvent.
3. The slurry according to claim 1 or 2, characterized in that The solvent is water, and the dispersant is a water-soluble dispersant; and / or The mass percentage of the hexagonal boron nitride powder is 15wt% to 30wt%; and / or The mass percentage of the dispersant is 3wt% to 8wt%.
4. The slurry according to claim 3, characterized in that The water-soluble dispersant includes at least one of a polyether dispersant, a polysorbate dispersant, and a cationic dispersant.
5. The slurry according to claim 4, characterized in that The polyether dispersant includes at least one of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether and polyether type hyperdispersant; and / or The polysorbate dispersant includes at least one of polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan monostearate; and / or the cationic dispersant includes at least one of hexadecyltrimethylammonium bromide and octadecyltrimethylammonium chloride.
6. The slurry according to claim 5, characterized in that The alkylphenol polyoxyethylene ether includes at least one of TX-10 and OP-10; and / or The fatty alcohol polyoxyethylene ether comprises AEO-9; and / or The polyether type hyperdispersant includes at least one of polyethylene glycol 400 and polyethylene glycol 3000.
7. The slurry according to claim 1 or 2, characterized in that: The adhesive includes at least one of polyvinyl alcohol (PVA), polyacrylate, polyacrylate emulsion, polyvinyl acetate emulsion and polyurethane.
8. The slurry according to claim 7, characterized in that The adhesive comprises polyvinyl alcohol (PVA), and the alcoholysis degree of the polyvinyl alcohol (PVA) ranges from 30% to 100%.
9. The slurry according to claim 1 or 2, characterized in that: The thickener includes polyacrylamide. Preferably, the weight average molecular weight of the polyacrylamide is 5 million to 20 million.
10. The slurry according to claim 1 or 2, characterized in that: The D50 particle size of the hexagonal boron nitride powder is 1 μm to 30 μm; and / or The hexagonal boron nitride powder is in the form of flakes or spheres.
11. The slurry according to claim 10, characterized in that The D50 particle size of the hexagonal boron nitride powder is 1 μm to 10 μm; or The D50 particle size of the hexagonal boron nitride powder is 15 μm to 25 μm.
12. The slurry according to any one of claims 1 to 11, characterized in that The viscosity of the slurry ranges from 1000 cps to 3000 cps.
13. A method for preparing a slurry, characterized in that: The steps include: According to the mass, 10 to 40 parts of hexagonal boron nitride powder, 1 to 10 parts of dispersant, 0.01 to 1 parts of thickener, 0.1 to 1 parts of adhesive and 45 to 90 parts of solvent are provided for standby use; The hexagonal boron nitride powder, dispersant, thickener, adhesive and solvent are stirred to prepare the slurry.
14. The method for preparing the slurry according to claim 13, characterized in that: The step of stirring the hexagonal boron nitride powder, dispersant, thickener, adhesive and solvent comprises the following steps: dissolving an adhesive in a solvent and stirring to obtain an adhesive solution; adding a dispersant to the adhesive solution to obtain a first dispersion; adding hexagonal boron nitride powder to the first dispersion and continuing stirring to obtain a second dispersion; Add the thickener to the second dispersion and continue stirring.
15. A substrate precursor, characterized in that: It comprises a green body and an isolation layer prepared by spraying a slurry prepared by the slurry as claimed in any one of claims 1 to 12 or the slurry preparation method as claimed in claim 13 or 14 on the surface of the green body.